"The hyena who stalks the capitalist deserts": imagining the 'anti-Bond' in the works of John le Carré. Issue 2 (23rd February 2023) - Oldham, Joseph
ABSTRACT: John le Carré's spy fiction has long been hailed as an 'opposite' to Ian Fleming's James Bond stories. This article re-examines this rivalry, first exploring how le Carré's breakthrough, The Spy Who Came in from the Cold (1963) subverts the conventional Bondian narrative. I then examine le Carré's development of a thesis on Bond as a figure whose consumerist qualities negated any moral core, an idea later developed into a subversion of the Bond persona in The Tailor of Panama (1996). Ultimately I argue that le Carré needed Bond as a rival against which to position his own oeuvre .